Forgone Earnings from Smoking : Evidence for a Developing Country - Lokshin, Michael; Beegle, Kathleen (World Bank, Washington, DC, 2012)
The authors estimate the economic losses related to the negative effect of smoking on wages in a context of a developing country. Using data from the 2005 Albania Living Standards Monitoring Survey, they jointly estimate a system of three equations: the smoking decision and two separate wage equations for smokers and nonsmokers. The results show that, after controlling for observed characteristics and taking into account unobserved heterogeneity in personal characteristics, smoking has a substantial negative impact on wages. On average smokers' wages are 20 percent lower than the wages of similar nonsmokers, providing strong evidence for the potential policy relevance of tobacco control initiatives for developing countries.